Anthropometric measures and their association with risk factors for cardio-metabolic diseases in Kenyan adults - F. Lajeunesse-Trempe; R. Dufour; P. du Souich; M. Paquette; L. U. Kaduka; D. L. Christensen (Taylor & Francis Group, 2018)
Background: The prevalence of cardio-metabolic diseases (CMD) is drastically increasing worldwide. Anthropometric measures of fat accumulation are correlated with CMD and Metabolic Syndrome (MS), but few studies have addressed this association in sub-Saharan African populations. Aim: To investigate the association between anthropometric features, MS and other CMD risk factors in a population from Kenya. Subjects and methods: In this cross-sectional study including 1405 Kenyans, anthropometric measurements including visceral adipose tissue (VAT) and abdominal subcutaneous adipose tissue (SAT) were carried out. Fasting blood glucose and standard oral glucose tolerance test, fasting serum insulin and plasma lipids were analysed. Homeostatic model assessment of insulin resistance was calculated. Systolic and diastolic blood pressures were measured. Results: CMD risk factors and MS were associated with all anthropometric features, except for high-density lipoprotein cholesterol levels (p < 0.05). The strongest association between MS and anthropometrics was seen with SAT (β = 1.45 ± 0.32 in men and 0.88 ± 0.14 in women, both p < 0.05). Conclusions: Anthropometric measures, especially features of central obesity such as VAT and SAT, are relevant indicators of cardio-metabolic health in Kenyan populations. SAT is the strongest predictor of MS. These results highlight the need for further research on the pathological implication of VAT and SAT, in order to understand patterns of fat distribution and cardio-metabolic health among different ethnic groups.